PENEGAKAN HUKUM TINDAK PIDANA PERTAMBANGAN TANPA IZIN DI INDONESIA - Marleno, Risma; Rumihin, Ony Frengky (Fakultas Hukum Universitas Narotama, 2026)
Law enforcement against illegal mining in Indonesia is an important issue because of its impact on the environment, economy, and community welfare. Illegal mining is a serious crime that can damage ecosystems, disrupt the sustainability of natural resources, and create social injustice. The legal framework governing illegal mining in Indonesia is regulated in Law No. 4 of 2009 concerning Mineral and Coal Mining (Minerba Law) and its subsequent regulations, as well as Law Law Number 32 of 2009 concerning Environmental Protection and Management (PPLH Law), which stipulates that mining activities can only be carried out by parties that have a valid permit from the government. Violations of these provisions are subject to criminal sanctions, both in the form of imprisonment and fines. The research method used in this study is a normative legal research method with a regulatory and conceptual approach. This study aims to examine the legal construction of unauthorized mining crimes based on Indonesian legislation. The results of the study show that even though there are strict regulations, law enforcement against illegal mining still faces various obstacles, including suboptimal supervision and low public awareness. Therefore, it is recommended that the government tighten supervision, increase socialization, and impose stricter sanctions to combat illegal mining. Keywords: Construction, Criminal Offenses, Mining